Moral judgment of genetic technologies: validation of the genetic technologies questionnaire in the German-speaking population - Teichmann, Birgit; Melchior, Florian; Beyreuther, Konrad; Chorianopoulou, Maria K. (Frontiers in Genetics, 2025)
IntroductionThe development of modern life sciences has expanded our biomedical capabilities to an unprecedented degree. For example, genetic testing can be used to predict hereditary predisposition or susceptibility to certain diseases. The development of gene scissors such as CRISPR/Cas makes it possible to repair the disease gene or introduce a protective gene in somatic cells but also in germline cells, leading to permanent changes of the genome. But is everything we “can” do morally justifiable? To what extent does the moral status of the living being, autonomy, and privacy influence the decision of whether something is morally “good” or “bad”? There is a lack of valid instruments to study the moral judgment of genetic technologies. Therefore, the aim of this study is to translate and validate the “Genetic Technologies Questionnaire” (GTQ) and the short version of the “Conventional Technologies Questionnaire” (CTQ5) into German.MethodsConvenience sampling (N = 317) was used to conduct a cross-sectional online study. Analyses included internal consistency, structural validity, known group construct validity, tests for floor and ceiling effects, and retest reliability with a subset of n = 69. Correlational analyses were conducted with education, age, prior knowledge of genetics, religiosity, conventional technologies, and prior genetic testing. This study used the STROBE checklist for reporting.ResultsThe GTQ30 (Cronbach’s α = 0.938) and GTQ20 (α = 0.940) are reliable and stable instruments for testing the moral judgment of lay people, while the GTQ5 (α = 0.857) and CTQ5 (α = 0.697) showed some weaknesses. Conventional technologies were judged morally better than genetic technologies, and genetic testing considered better than genome editing. Two additional versions were validated: the GTQ-Human (GTQ-H), using all items relating to humans, and the GTQ-Moral Status (GTQ-MS), including one item per different group of living beings for genetic testing and one for genome editing.ConclusionThe GTQ is a valid instrument that is now available in shorter versions for different areas of research: the GTQ-MS for philosophical questions addressing moral status and the GTQ-H for biomedical and psychological questions related to research, prognosis, diagnosis, and therapy in humans.